2020
DOI: 10.1016/j.buildenv.2019.106505
|View full text |Cite
|
Sign up to set email alerts
|

Building fault detection and diagnostics: Achieved savings, and methods to evaluate algorithm performance

Abstract: Fault detection and diagnosis (FDD) represents one of the most active areas of research and commercial product development in the buildings industry. This paper addresses two questions concerning FDD implementation and advancement 1) What are today's users of FDD saving and spending on the technology? 2) What methods and datasets can be used to evaluate and benchmark FDD algorithm performance? Relevant to the first question, 26 organizations that use FDD across a total 550 buildings and 97M sf achieved median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…These results are similar to a 2019 paper by LBNL which calculated an 8% median site energy savings based on data from 550 buildings where MBCx was implemented with the support of software-based FDD (Lin, Kramer, and Granderson 2020). The LBNL study found a median (Loftness et al 2020).…”
Section: The Business Case For Monitoring-based Commissioningsupporting
confidence: 83%
“…These results are similar to a 2019 paper by LBNL which calculated an 8% median site energy savings based on data from 550 buildings where MBCx was implemented with the support of software-based FDD (Lin, Kramer, and Granderson 2020). The LBNL study found a median (Loftness et al 2020).…”
Section: The Business Case For Monitoring-based Commissioningsupporting
confidence: 83%
“…3 While many agencies already utilize various free software tools (such as the U.S. Environmental Protection Agency's ENERGY STAR ® Portfolio Manager for benchmarking), commercially available EMIS tools offer agencies enhanced benefits that justify the investment required to achieve these savings. Further, SEAC results show high returns on EMIS investment (Lin, Kramer, and Granderson 2020). In 2020, for campaign participants who implemented AFDD, median annual savings were $0.27 per square foot, compared to deployment and recurring costs of $0.05 and $0.07 per square foot, respectively (Lin, Kramer, and Granderson).…”
Section: Direct Valuementioning
confidence: 99%
“…AFDD is the process of identifying (detecting) deviations from normal or expected operation (faults) and resolving (diagnosing) the type of problem or its location (Lin, Kramer, and Granderson 2020). AFDD is an advanced EMIS capability that uses algorithms to detect equipment-level or system-level faults and diagnose their causes.…”
Section: Automated Fault Detection and Diagnosticsmentioning
confidence: 99%
“…After the survey, the initial hardware and software architecture of the EMIS can be designed and used to create a budget, business case, and obtain necessary approvals. When the budget is assembled it should include all costs inherent to an EMIS solution, including: (Lin, Kramer, and Granderson 2020;Kramer et al 2019b).…”
Section: Establish Feasibilitymentioning
confidence: 99%